2019
DOI: 10.1177/1060028019865873
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Dosing for Critically Ill Adult Patients Receiving Intermittent Hemodialysis, Prolonged Intermittent Renal Replacement Therapy, and Continuous Renal Replacement Therapy: An Update

Abstract: Objective: To summarize current antibiotic dosing recommendations in critically ill patients receiving intermittent hemodialysis (IHD), prolonged intermittent renal replacement therapy (PIRRT), and continuous renal replacement therapy (CRRT), including considerations for individualizing therapy. Data Sources: A literature search of PubMed from January 2008 to May 2019 was performed to identify English-language literature in which dosing recommendations were proposed for antibiotics commonly used in critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 99 publications
0
98
1
Order By: Relevance
“…Finally, we also assessed the effect of protein binding and adsorption on the clearance of apixaban during CRRT. Although protein binding is known to be one of the most important factors affecting drug removal during CRRT [76], exceedingly few agents have available data regarding binding to bovine plasma as these animals are not typically utilized in the drug development process [77]. As the measured protein binding of apixaban in bovine plasma in our study was within ~25% of that observed in healthy volunteers, it is unlikely that this signi cantly altered our optimal dosing recommendations.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, we also assessed the effect of protein binding and adsorption on the clearance of apixaban during CRRT. Although protein binding is known to be one of the most important factors affecting drug removal during CRRT [76], exceedingly few agents have available data regarding binding to bovine plasma as these animals are not typically utilized in the drug development process [77]. As the measured protein binding of apixaban in bovine plasma in our study was within ~25% of that observed in healthy volunteers, it is unlikely that this signi cantly altered our optimal dosing recommendations.…”
Section: Discussionmentioning
confidence: 73%
“…The effect of different CRRT‐techniques, convection vs diffusion, modes and settings on pharmacokinetics of antibiotics including vancomycin is not finally established 18‐20 . Although several population pharmacokinetic‐pharmacodynamic (PK‐PD) models for vancomycin exist, many are based on smaller, often retrospective studies, and are not updated regarding CRRT‐filters, mode and CRRT‐dose, with few and not consecutively collected vancomycin levels 17,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we also assessed protein binding, adsorption, and the effects of point of replacement uid dilution on drug removal. Although protein binding is known to be one of the most important factors affecting drug removal during CRRT [80], exceedingly few agents have available data regarding binding to bovine plasma as these animals are not typically utilized in the drug development process [81]. As such, it is crucial to directly measure this for appropriate clinical translation of in vitro results.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed degrees of lter adsorption high enough to potentially effect drug dosing during CRRT in addition to ltration, particularly for the HF1400 lter. Although the effect of point of replacement uid dilution during CVVH is largely ignored from CRRT dosing recommendations [80,82], the impact can be signi cant, especially at high ow rates [52], and warrants thorough evaluation such as ours during in vitro studies.…”
Section: Discussionmentioning
confidence: 99%